2023
DOI: 10.1177/00031348231204914
|View full text |Cite
|
Sign up to set email alerts
|

Key Findings on Computed Tomography of the Head that Predict Death or the Need for Neurosurgical Intervention From Traumatic Brain Injury

Soroosh Noorbakhsh,
Michael Keirsey,
Alexis Hess
et al.

Abstract: Background Traumatic brain injury (TBI) requires rapid management to avoid secondary injury or death. This study evaluated if a simple schema for quickly interpreting CT head (CTH) imaging by trauma surgeons and trainees could be validated to predict need for neurosurgical intervention (NSI) or death from TBI within 24 hours. Methods We retrospectively reviewed TBI patients presenting to our trauma center in 2020 with blunt mechanism and GCS ≤ 12. Primary independent variables were presence of 7 normal finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Mortality rates that are directly associated with TBI include death resulting from the initial injury in the acute phase, within hours to days of the incident. Research studies have investigated the predictors for immediate impact of TBI on mortality such as the severity of injury, GCS, neuroimaging findings and type of injury [12,13]. For example, studies have shown that subjects with penetrating TBI show higher mortality rates in comparison to blunt TBI [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates that are directly associated with TBI include death resulting from the initial injury in the acute phase, within hours to days of the incident. Research studies have investigated the predictors for immediate impact of TBI on mortality such as the severity of injury, GCS, neuroimaging findings and type of injury [12,13]. For example, studies have shown that subjects with penetrating TBI show higher mortality rates in comparison to blunt TBI [14].…”
Section: Introductionmentioning
confidence: 99%